Occurrence of Intestinal Helminths Among Children Attending Primary Schools in Yorro and Zing Local Government Areas of Taraba State - Garba Paul; Allahnanan Emmanuel; Houmsou Robert Soumay; Zakari Nasiru Ishaq (Journal of Multidisciplinary Science: MIKAILALSYS, 2025)
Intestinal helminthic infections (IHIs) remain a major public health concern, particularly among school-aged children in resource-limited settings. This study examines the occurrence, risk factors, and socio-demographic determinants of IHIs among primary school children in Yorro and Zing Local Government Areas (LGAs) of Taraba State, Nigeria. A cross-sectional survey was conducted with 500 randomly selected pupils, and stool samples were analyzed using standard parasitological techniques. The overall prevalence of intestinal helminths was 75.7%, with Yorro LGA recording a higher rate (78.8%) than Zing LGA (72.7%). No statistically significant difference was observed between boys (76.4%) and girls (74.8%) (p > 0.05). The high prevalence underscores the urgent need for strengthened public health measures, including regular mass deworming, improved sanitation facilities, access to safe drinking water, and targeted health education for schoolchildren, parents, and teachers to reduce transmission and reinfection rates.